(untitled) (jornal of the libyan geographical society, 2016)
The problem of wastewater disposal has become one of the most important problems facing countries worldwide, especially developing countries, and particularly those outside urban centers, due to the environmental and human health risks it poses, even indirectly, not to mention its economic costs. The citizen suffers in the absence of infrastructure, as sewage water contains many dangerous pollutants, whether organic or chemical substances such as soap, and industrial waste (in addition to many types of harmful bacteria and microbes and toxic liquids...etc.). Wastewater, whether domestic or industrial, plays a significant role in exacerbating environmental problems, which have direct negative repercussions on water and soil, and even indirectly on humans. To highlight the dangers of these negative effects, it is essential to study them, research their causes, and find ways to address them. Therefore, it is necessary to quickly take practical measures regarding this, not only by building sewage networks but also by building treatment plants for this water, in order to avoid the spread of its pollutants on the one hand, and to benefit from its water after getting rid of its impurities and pollutants on the other hand.